The Tirzepatide Drop: Beware of Slimmer's Paralysis - John M. Tucker MD; Jordan Ritchie MD (SAGE Publishing, 2024)
This case series explores the association between tirzepatide-assisted weight loss and the development of foot drop due to peroneal nerve neuropathy, a phenomenon known as slimmer's paralysis. Two cases are presented of patients who experienced rapid weight loss after initiation of tirzepatide therapy and within 6 to 8 months developed bilateral foot drop. As providers, we have more medications than ever to assist patients in their weight loss journeys, but both of these cases are reminders of the risks of rapid weight loss and the need to monitor therapy closely for patients on tirzepatide and similar medications.